CD3+ graft cell count influence on chronic GVHD in haploidentical allogeneic transplantation using post-transplant cyclophosphamide. (December 2018) - Mussetti, A; Philippis, C; Carniti, C; Bastos-Oreiro, M; Gayoso, J; Cieri, N; Pennisi, M; Ciceri, F; Greco, R; Peccatori, J; Patriarca, F; Mariotti, J; et al.
Abstract The effects of graft or donor characteristics in haploidentical hematopoietic cell transplantation (HCT) using post-transplant cyclophosphamide (PT-Cy) are largely unknown. In this multicenter retrospective study we analyzed the correlations between graft cell composition (CD34+, CD3+) and donor features on transplant outcomes in 234 patients who underwent HCT between 2010 and 2016. On multivariate analysis, the use of peripheral blood stem cells (PBSC) was associated with an increased incidence of grade 2–4 acute GVHD [HR 1.94, 95% confidence Interval (CI) = 1.01–3.98, p  = 0.05]. An elevated CD3+ graft content was associated with an increased incidence of all-grade chronic GVHD [HR 1.36 (95% CI = 1.06–1.74), p  = 0.01]. This effect was confirmed only for the PBSC graft group. A higher CD34+ graft content had a protective role on non-relapse mortality [HR 0.78 (95% CI = 0.62–0.96), p  = 0.02] but this was confirmed only for the bone marrow (BM)-derived graft cohort. Donor characteristics did not influence any outcomes. GVHD prophylaxis should be modulated accordingly to CD3+ graft content, especially when a PBSC graft is used. These results need further validation in prospective trials.